Bringing what state back in? Neo-Marxism and the origin of the Committee on States and Social Structures - Khachaturian, Rafael (Political Research Quarterly)
This article examines the interdisciplinary movement to (3z(Bbring the state back in,(3y (Badvanced during the 1980s by the Committee on States and Social Structures. Drawing on the Committee$1 (Bs archives at the Social Science Research Council, I show that its influential neo-Weberian conception of the state was developed in dialogue with earlier neo-Marxist debates about the capitalist state. However, its interpretation of neo-Marxism as a class reductive and functionalist variant of (3z(Bgrand theory(3y (Balso created a narrative that marginalized the latter$1 (Bs contributions to the literature on the state. This displacement had lasting consequences, for while neo-Marxist approaches had provided a critical perspective on the relationship between the social sciences and the state, the Committee$1 (Bs narrative had a depoliticizing effect on this subject matter. Reconstructing this moment both recovers the forgotten influence of the New Left and neo-Marxist scholarship on postwar political science and sociology, and elaborates on the contested history of the state as a political concept. - Reproduced.s